Fabrication Of Porcelain Grinding Media Made Of Locally Processed Clay - Hamisan, Fairuz (Universiti Sains Malaysia, 2017)
The aim of this research is to fabricate locally processed clay produced low firing temperature porcelain balls as grinding media with superior mechanical and physical properties than the similar commercially available grinding media. In this study, locally processed clay from Trong (Taiping, Perak) was used as main raw material to make the porcelain grinding media by addition with kaolin, potash feldspar and quartz. The objectives of this study were to fabricate porcelain grinding media by utilizing locally processed clay with different composition and firing temperature. Five different raw material compositions (CB1, CB2, CB3, CB4 and CB5) were prepared. The slip viscosity was measured by viscometer. Slip casting was used as shaping technique. After the casting process, the casted product were dried at 90°C for two days before firing at three different firing temperature (1150°C,1200°C,1250°C) with 1 hour soaking time (5°C/min heating and cooling rate). Fired products were characterized with physical observation, shrinkage measurement, bulk density and porosity measurement by Archimedes principle and the performance of grinding media will evaluate via milling silica sand (particle size: 1000 μm) for 4 hours. Overall, CB1 samples fired at 1250°C have shown the highest shrinkage (9.94%) with high bulk density (2.31g/cm3), lowest apparent porosity (4.79%) and higher hardeness (5.6 GPa). This is because formation of glassy phase. CB1 samples also produce the finest particle of silica sand (6.85 μm) after the milling process. This is due to the highest density of the fired porcelain grinding media (2.31g/cm3) which give the effective xvi impact force during the milling process. Therefore, this research proved that has potential to fabricate porcelain grinding media.